High-efficiency electrochemical biosensor for myocardial infarction detection
By constructing an electrochemical immunosensor using screen-printed electrodes and substrate materials/PtAg nanocomposites, the problems of signal drift, electrode passivation and poor biocompatibility in the prior art are solved, and efficient, stable and sensitive biomarker detection is achieved.
Patent Information
- Application Number
- CN202411714139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the early monitoring of myocardial infarction, existing electrochemical sensors have problems such as signal drift, electrode surface passivation and contamination, difficulty in detecting multiple targets at the same time, poor biocompatibility and weak electron transmission capabilities.
Using screen-printed electrodes as substrates, four label-free cTnI and microRNA electrochemical immunosensors were constructed through material design, using substrate material/PtAg nanocomposites, including MXene or p-COF as substrate materials, combined with PtAg nanoparticles or nanofibers to form an efficient electrochemical immunosensor.
Efficient, stable and sensitive biomarker detection is achieved, especially in the detection of myocardial infarction and sepsis markers, improving the biocompatibility and electron transmission capabilities of the sensor, reducing detection costs and time.
Smart Images

Figure CN119715732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine, and in particular to research on a novel high-efficiency electrochemical biosensor for myocardial infarction detection. Background Art
[0002] Early diagnosis of acute myocardial infarction (AMI) is of great significance in reducing mortality. Usually, clinicians use three diagnostic criteria to determine whether a patient has AMI, including clinical symptoms such as persistent chest pain, dynamic ST-T changes in electrocardiogram (ECG), and dynamic increases in myocardial infarction markers such as cardiac troponin I (cTnI), creatine kinase-MB (CK-MB), and myoglobin (Mb). In recent years, some specific microRNAs such as microRNA-133a have shown significant expression in the early stages of AMI. Compared with the complexity of laboratory blood tests, expensive instruments and equipment, and long time consumption, point-of-care testing (POCT) has unique advantages such as simple preparation, rapid analysis, low cost, portable size, rapid acquisition of on-site test results, and convenient and timely decision-making. In recent years, it has received widespread attention in clinical and bedside testing. Among them, electrochemical biosensors have become an emerging technology for target detection in complex media due to their convenient preparation, signal sensitivity, and miniaturization. They are also an important way to achieve POCT. However, in the electrochemical signal amplification strategy, most of them use a three-electrode system with an expensive Au substrate, which undoubtedly increases the cost of use and has poor reusability. Although metal nanoparticles (MNPs) and metal oxide nanomaterials have received extensive attention as optional materials in the fields of catalysis, energy conversion and storage, environmental technology, and biological applications. These nanocatalysts have high specific surface area, abundant active sites, and unique electronic properties, and have excellent catalytic ability. In particular, rare MNPs (Au NPs, PtNPs, etc.) functionalized electrochemical biosensors have been established for immunosensing of low-concentration immune markers. However, in the catalytic process, multi-molecule migration-coalescing caused by high surface energy is usually an inevitable inactivation.
[0003] In recent years, continuous real-time sensing has received widespread attention in biomarker monitoring. Most of the currently used methods, such as chromatography, immunoassay, or mass spectrometry, have the disadvantage of high instrument costs. In addition, in actual use, high levels of sample handling and processing are often required, delaying the availability of test results.
[0004] The demand for POCT (Point of Care Testing) sensing devices has exploded, and has great application potential in early monitoring and clinical diagnosis of myocardial infarction. Electrochemical sensors can be suitable candidates for continuous biomarker measurement due to their low cost, easy operation, and high sensitivity. However, the development of continuous detection electrochemical sensors has the following problems: (i) signal drift caused by changes in environmental conditions; (ii) electrode surface passivation and contamination after long-term exposure to complex samples; (iii) difficulty in detecting multiple targets simultaneously; (iv) poor biocompatibility; (v) introduction of additional sensing agents reduces electrode stability; and (vi) weak electron transfer capacity. Summary of the invention
[0005] The present invention aims to overcome the above-mentioned defects, and uses screen-printed electrodes (SPEC) as substrates, and through material design, constructs four types of label-free cTnI and microRNA electrochemical immunosensors with excellent detection performance.
[0006] The application of the substrate material / PtAg nanocomposite material provided by the present invention in constructing an electrochemical immunosensor is characterized by:
[0007] The above-mentioned base material is selected from MXene or p-COF.
[0008] Furthermore, the application provided by the present invention is characterized in that:
[0009] The electrochemical immunosensor identifies / detects / sensits myocardial infarction markers and / or sepsis markers.
[0010] Furthermore, the application provided by the present invention is characterized in that:
[0011] The electrochemical immunosensor detects miRNAs and / or cTnI.
[0012] Furthermore, the application provided by the present invention is characterized in that:
[0013] The electrochemical immunosensor described above detects serum samples.
[0014] Furthermore, the present invention also provides a substrate material / PtAg nanocomposite material for constructing an electrochemical immunosensor, characterized in that:
[0015] The substrate material / PtAg nanocomposite material is MXene / PtAg NPs, or MXene / PtAg NWs, or p-COF / PtAg NPs, or p-COF / PtAg NWs;
[0016] Wherein, the above-mentioned MXene / PtAg NPs is a composite material of MXene and PtAg NPs with an accordion structure;
[0017] The above-mentioned MXene / PtAg NWs is a composite material of MXene and PtAg NWs with an accordion structure;
[0018] The above-mentioned p-COF / PtAg NPs is a composite material of p-COF and PtAg NPs;
[0019] The above-mentioned p-COF / PtAg NWs is a composite material of p-COF and PtAg NWs.
[0020] Furthermore, the substrate material / PtAg nanocomposite material provided by the present invention is also characterized in that:
[0021] The above-mentioned MXene NSs are MXenes modified by APTES amination.
[0022] Furthermore, the substrate material / PtAg nanocomposite material provided by the present invention is also characterized in that:
[0023] The above-mentioned MXene is obtained by etching MAX-Ti3AlC2 using LiF and hydrochloric acid solution as etching solutions.
[0024] Furthermore, the substrate material / PtAg nanocomposite material provided by the present invention is also characterized in that:
[0025] The preparation method of the above MXene / PtAg NPs is as follows: dissolving MXene NSs and CTAB in deionized water and performing ultrasonic treatment until they are completely dissolved; dissolving H2PtCl6 and AgNO3 solutions in the above mixed solution; stirring the mixture at a temperature of 90-100°C for 10-60 minutes; then, rapidly injecting AA; continuing to stir the mixture at a temperature of 90-100°C for 90-120 minutes; and finally obtaining MXene / PtAg NPs after centrifugation, washing, and drying.
[0026] The preparation method of the above MXene / PtAg NWs is as follows: dissolving MXene NSs in an EG solution of H2PtCl6 and AgNO3; adding a mixed solution of EG and DMF, and magnetically stirring until the mixed solution turns light yellow; then dissolving KOH in the above mixture, and magnetically stirring until KOH is completely dissolved to form a black-green uniform solution; then, reacting the mixed solution in an autoclave at a temperature of 150-190°C for 2-6 hours; finally, obtaining MXene / PtAg NWs after centrifugation, washing, and drying;
[0027] The preparation method of the p-COF / PtAg NPs is as follows: p-COF and CTAB are dissolved in deionized water and treated by ultrasound until they are completely dissolved; H2PtCl6 and AgNO3 solutions are dissolved in the mixed solution; the mixture is stirred at 90-100°C for 10-60 minutes; then, AA is quickly injected; the mixture is kept at 90-100°C for 90-120 minutes; finally, p-COF / PtAg NPs are obtained after centrifugation, washing and drying;
[0028] The above-mentioned p-COF / PtAg NWs are prepared by dissolving p-COF in an EG solution of H2PtCl6 and AgNO3; adding a mixed solution of EG and DMF, and magnetically stirring until the mixed solution turns light yellow; then dissolving KOH in the above-mentioned mixture, and magnetically stirring until KOH is completely dissolved to form a black-green uniform solution; thereafter, reacting the mixed solution in an autoclave at a temperature of 150-190°C for 2-6 hours; finally, obtaining p-COF / PtAg NWs after centrifugation, washing, and drying.
[0029] Furthermore, the substrate material / PtAg nanocomposite material provided by the present invention is also characterized in that:
[0030] The molar ratio of the above H2PtCl6 and AgNO3 is 7:1-5.
[0031] Furthermore, the substrate material / PtAg nanocomposite material provided by the present invention is also characterized in that:
[0032] The method for constructing the electrochemical immunosensor is as follows: EDC and NHS are added to the prepared cardiac troponin antibody Ab solution, and the solution is placed on a shaker for 10-20 minutes to activate the surface carboxyl groups of the antibody; the activated Ab solution is dripped onto the surface of the SPEC / substrate material / PtAg nanocomposite electrode, and the reaction is incubated at 37°C for 60-100 minutes. After the reaction is completed, PBS is used for washing, and BSA is dripped onto the electrode surface for incubation for 30-60 minutes to block the surface active sites; finally, PBS is used to wash away the unbound BSA to obtain the SPEC / substrate material / PtAg nanocomposite / Ab / BSA electrode.
[0033] Furthermore, the substrate material / PtAg nanocomposite material provided by the present invention is also characterized in that:
[0034] When the electrochemical immunosensor is used to detect microRNA-133a, the incubation method of the electrode is as follows: the substrate material / PtAg nanocomposite solution is titrated on the working electrode, and after drying using a constant temperature heating stage, the customized anti-microRNA-133a DNA sequence probe is attached to the surface of the SPEC working electrode deposited with the substrate material / PtAg nanocomposite, and the probe is customized with C6-SH at the "5'-" end and methylene blue at the "3'-" end.
[0035] Furthermore, the substrate material / PtAg nanocomposite material provided by the present invention is also characterized in that:
[0036] The above-mentioned base material / PtAg nanocomposite material is coated with a CQDs@PDA antifouling coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 .SPEC electrode and sensing material deposition status;
[0038] Figure 2 . Cyclic voltammetry curves of (a) rGO, (b) MoS2, (c) MXene@ZnIn2S4, (d) ZnIn2S4, (e) MXene and (f) COF
[0039] Figure 3 Differential pulse voltammetry curves of (a) rGO, (b) MoS2, (c) MXene@ZnIn2S4, (d) ZnIn2S4, (e) MXene and (f) COF
[0040] Figure 4 (a, c) BET and (b, d) pore size distribution diagrams of MXene and p-COF;
[0041] Figure 5 .TAFEL slope of the substrate material (kinetic analysis);
[0042] Figure 6 .Schematic diagram of the construction of SPEC / MXene / PtAg NPs / Ab / BSA electrochemical immunosensor;
[0043] Figure 7 (a) SEM image, (b) XRD pattern and XPS (c) Ti 2p orbital and (d) C 1s orbital spectrum of accordion-shaped MXene substrate
[0044] Figure 8 .(a) XPS full spectrum and (b) XRD patterns of MXene substrate and MXene / PtAg NPs and NWs;
[0045] Fig. 9 . Verification of amine groups, including (a) Zeta potential measurement results of MXene, APTES / MXene, PtAg NPs, MXene / PtAg NPs, PtAg NWs and MXene / PtAg NWs; (b) Ti 2p and (c) C 1s orbital spectra of MXene / PtAg NWs; (d) EPR analysis of MXene, MXene / PtAg NPs and MXene / PtAg NWs; (e) Pt4f and (f) Ag 3d orbital spectra of MXene / PtAg NWs; Fig.10 .XPS N 1s orbital spectra of (a) APTES / MXene / PtAg NWs, (b) APTES / MXene NSs and (c) MXene NSs; Fig.11 . (a) TAFEL slope of SPEC / MXene / PtAg NPs and (b) SPEC / MXene / PtAg NWs; (c) CV and (d) DPV tests of SPEC / MXene / PtAg NWs; XRD (e) full spectrum and (f) thumbnail of MXene / PtAg NWs at different doping ratios;
[0046] Fig.12 . Effects of (a) [Fe(CN)6]3- / 4 concentration (b) cTnI antibody incubation time and (c) BSA incubation time on the current density of the immunosensor;
[0047] Fig.13 .(a) Current response of the electrode assembly process: (B) SPEC, (D) SPEC / MXene, (F) SPEC / MXene / PtAg NWs, (H) SPEC / MXene / PtAg NWs / anti-cTnI, (J) SPEC / MXene / PtAg NWs / anti-cTnI / BSA, (L) SPEC / MXene / PtAg NWs / anti-cTnI / BSA / cTnI and (b) EIS Nyquist spectra;
[0048] Fig.14 .(ab) Stability and (cd) reproducibility of SPEC / MXene / PtAg NPs and SPEC / MXene / PtAg NWs;
[0049] Fig.15 SPEC / MXene / PtAg NPs-based immunosensor (a) Peak current response under gradient cTnI antigen concentration, (b) Linear fitting relationship between (I0-I) / I0 and the logarithm of cTnI concentration, (c) Selectivity and (d) Long-term stability;
[0050] Fig.16 SPEC / MXene / PtAg NWs-based immunosensor (a) Peak current response under gradient cTnI antigen concentration, (b) linear fitting relationship between (I0-I) / I0 and the logarithm of cTnI concentration, (c) selectivity and (d) long-term stability;
[0051] Fig.17 .100mV s-1-600mV s-1 cyclic voltammetry scan curves of (a) bare SPEC electrode, (b) SPEC / MXene, (c) SPEC / MXene / PtAg NPs, and (d) SPEC / MXene / PtAg NWs; (e) ECSA active specific surface area fitting; (f) EIS impedance spectrum analysis;
[0052] Fig.18 Gradient test of real serum (a) peak current change and (b) cubic polynomial fitting curve;
[0053] Fig.19 .(a) FT-IR characterization of TA, TAPP and p-COF; (b) XPS full spectra of p-COF and p-COF / PtAg NWs; (c) XRD full spectra of p-COF, p-COF / PtAg NPs, p-COF / PtAg NWs and (d) 0-15° XRD thumbnail of p-COF;
[0054] Fig. 20 (a) SEM and (b) TEM images of p-COF; (c) TEM, (d) SEM, (e) HRTEM and (f) SAED images of p-COF / PtAg NWs; (gh) SEM and (i) TEM images of p-COF / PtAg NWs
[0055] Fig.21 .(a) Zeta potential measurement results of p-COF, PtAg NPs, p-COF / PtAg NPs, PtAg NWs and p-COF / PtAg NWs; XPS (b) N 1s, (c) C 1s, (d) full spectrum, (e) Pt 4f and (f) Ag 3d orbital spectra of p-COF / PtAg NWs;
[0056] Fig. 22(a) Peak current response of the electrode assembly process: (i) SPEC, (ii) SPEC / p-COF, (iii) SPEC / p-COF / PtAg NWs, (iv) SPEC / p-COF / PtAg NWs / Ab, (v) SPEC / p-COF / PtAg NWs / Ab / BSA, (vi) SPEC / p-COF / PtAg NWs / Ab / BSA / Ag and (b) EIS Nyquist spectra;
[0057] Fig.23 .(a) IT stability test, (b) current gain and (cd) reproducibility display of SPEC / p-COF / PtAg NPs and SPEC / p-COF / PtAg NWs immunosensors;
[0058] Fig.24 SPEC / p-COF / PtAg NPs-based immunosensor (a) Peak current response under gradient cTnI antigen concentration, (b) Linear fitting relationship between I and the logarithm of cTnI concentration, (c) Selectivity and (d) Long-term stability;
[0059] Fig.25 SPEC / p-COF / PtAg NWs-based immunosensor (a) Peak current response under gradient cTnI antigen concentration, (b) Linear fitting relationship between I and logarithm of cTnI concentration, (c) Selectivity and (d) Long-term stability;
[0060] Fig.26 . (a) Peak current response of cTnI at different concentrations and (b) linear relationship between I) and the logarithm of cTnI concentration based on SPEC / p-COF / PtAg NWs immunosensor;
[0061] Fig. 27 .Schematic diagram of the process of SPEC electrode incubation and measurement of microRNA-133a;
[0062] Fig.28 . (a) Peak current response of microRNA-133a with different concentrations in PBS and (b) linear relationship between I and the logarithm of microRNA-133a concentration based on SPEC / p-COF / PtAg NWs immunosensor;
[0063] Fig.29 . (a) Peak current response of microRNA-133a measured at different dilutions in real serum based on SPEC / p-COF / PtAg NWs immunosensor and (b) linear relationship between I and logarithm of microRNA-133a concentration;
[0064] Fig.30 . Current loss efficiency of four anti-fouling coating materials: (a) CQDs, (b) CS, (c) rGO, and (d) SWNT;
[0065] Fig.31 Peak current loss efficiency of CQDs in (a) Mb, (b) CRP, (c) CK and (d) BSA environments;
[0066] Fig.32 .Clinical serum test (cTnI) under the action of CQDs@PDA self-cleaning coating;
[0067] Fig.33 .Clinical serum test (microRNA) under the action of CQDs@PDA self-cleaning coating;
[0068] Fig.34 (a) Comparison of peak current loss efficiency within 10 days before and after incubation of CQDs@PDA (antifouling property) and (bd) recognition ability of the immunosensing platform functionalized with self-cleaning coating in real serum of patients DETAILED DESCRIPTION
[0069] The present invention is capable of various modifications and various embodiments, and therefore specific embodiments are illustrated and described in the accompanying drawings. However, this is not intended to limit the present invention to specific implementations, but should be understood to include all modifications, equivalents, and even substitutes that fall within the concept and technical scope of the present invention.
[0070] Example 1. Screening of substrates and electrochemically active materials
[0071] Nanomaterials have different electrical properties. In order to screen out suitable electrical substrate materials, this example selected seven nanosubstrates with large specific surface areas and immune conditions. Two nanoporous materials with large current density were determined through electrical tests. Subsequently, in order to increase the electrochemical activity and make full use of the EC sensing advantages, the morphology of precious metal alloy nanocrystals was regulated and made to grow in situ on the surface or inner cavity of the screened substrate material, providing a research basis for subsequent immune marker analysis.
[0072] 1.1 Performance Testing
[0073] 1.1.1 Construction of SPEC flexible electrochemical sensor
[0074] Weigh 10 mg of the sensing material and dissolve it in 5 mL of deionized water. Ultrasonic treatment was performed at 90% power for 5 min. The SPEC electrode cleaned with anhydrous ethanol was spread flat on a constant temperature heating table at 85 ° C. 10 μL of the prepared solution was pipetted with a pipette and evenly deposited on the surface of the SPEC working electrode. A vortex instrument was used to oscillate for 30 seconds before the deposition was completed. After the deposition was completed, the electrochemical workstation Chenhua 660e was used to measure in a PBS electrolyte containing 5 mM NaCl2 and 5 mM [Fe (CN) 6] 3- / 4-. The deposition state is as follows Figure 1 shown.
[0075] 1.1.2 Test Method
[0076] The electrical properties of the electrodes were tested using the Chenhua 660e electrochemical workstation. The SPEC electrodes packaged in the previous step are also three-electrode systems, in which conductive silver paste is used for printing the conductor pattern, conductive carbon (C) paste is used for printing the counter electrode and working electrode patterns, and silver / silver chloride (Ag / AgCl) paste is used for printing the reference electrode pattern. The SPEC detection process uses simulated human body fluid pH (pH = 7.4) and room temperature testing. The electrolyte solvent is PBS (0.01M, pH = 7.2) solution containing KCl. The electrolyte in the entire electrochemical test process is the above PBS solution containing 5mM NaCl2 and 5mM [Fe(CN)6]3- / 4-. In order to characterize the reversibility of the sensing system, multi-dimensional test analysis was performed on the bare SPEC electrode, the electrode covered with a conductive substrate material, and the electrode with a functionalized precious metal-loaded nanocomposite material. The specific test items and experimental parameters are as follows:
[0077] (1) Linear Sweep Voltammetry (LSV) was used to obtain the voltammetric relationship between electrode current and electrode potential. The linear sweep voltammetric potential scanning range was -1V to 1V, and the scanning rate was set to 100mV s-1.
[0078] (2) Electrochemical Impedance Spectroscopy (EIS), Nyquist plot is an important tool for studying electrode process dynamics, electrode surface phenomena, and measuring solid electrolyte conductivity. Its arc radius reflects the charge transfer resistance (Rct), which can analyze the charge transfer dynamics, charge transport and diffusion processes at the electrode / electrolyte interface reaction. The smaller the impedance spectrum arc radius, the better the electron-hole separation effect. During the test, the amplitude was set to 10mV and the frequency range was 106Hz to 0.1Hz.
[0079] (3) Cyclic voltammetry (CV) is a widely used method to study the kinetics and thermodynamic properties of electrochemical reactions, as well as the electrochemical behavior of surfactants. This technique is achieved by applying a varying potential to the electrode surface and measuring the corresponding current response. CV usually uses a controllable potential scanner to change the electrode potential linearly over time, and then measures the resulting current. By recording the relationship between current and potential, information about the reaction kinetics and thermodynamic properties can be obtained. The potential scan range is -1V to 1V, and the initial scan rate is set to 100mV s-1, which is then gradually increased to 600mV s-1.
[0080] (4) Differential Pulse Voltammetry (DPV) is an electrochemical analysis technique and an improved form of pulse voltammetry. It combines the advantages of pulse voltammetry and differential voltammetry and is used to detect and analyze electrochemical reactions in solutions. In DPV, the electrode potential changes linearly or nonlinearly in a series of pulses, with a certain interval between each pulse. At the end of each pulse, the current generated is measured. Compared with the reference electrode, a current difference will be generated, which reflects the electrochemical reaction that occurred during the potential change. Therefore, in this project, it plays an important role in the quantitative analysis of the serum, microRNA and cTnI to be tested. By linearly fitting the biomarkers with known concentration gradients, the sensitivity and detection limit of the immunosensor can be calculated. Based on the inherent characteristics of the existing SPEC electrode, the test parameters were set to -0.3V-0.5V.
[0081] (5) Open Circuit Voltage (OPCT): The parameter setting is to select the bias voltage of the curve when it lasts for 400 s or when it is continuously stable. OPCT is a necessary condition for measuring EIS.
[0082] (6) TAFEL slope is widely used in electrochemical research to analyze the rate-controlling step of electrochemical reactions, interfacial kinetic behavior, and reaction mechanisms in electrochemical processes. The test process parameters are selected in the ±0.5 V range under the condition of It stability.
[0083] 1.2. Screening of electrical properties of substrate materials
[0084] The current density of the SPEC bare electrode and the seven prepared electroactive materials were measured by cyclic voltammetry (CV), such as Figure 2As shown, the oxidation / reduction peaks of the seven electrode materials are clear and obvious, symmetrical and uniform without interference, indicating the reversibility of the redox reaction process, which meets the premise of constructing the immunosensor. The current density (peak area) increases to varying degrees. High current density can increase the intensity of the electrochemical signal, thereby improving the sensitivity of the sensor. Obviously, MXene and p-COF have the best gain effect.
[0085] The relationship between current and voltage is measured using differential pulse voltammetry (DPV). In the field of biosensing, DPV plays an indispensable and important role. It is mainly used to analyze electrochemically active substances in solutions, such as the detection of electroactive substances, determination of their concentrations, and study of their reaction kinetics. It has the characteristics of high sensitivity, high selectivity, and high resolution. Figure 3 As shown in the figure, under the condition of SPEC bare electrode, its peak current response is 166μA / cm2. After the deposition of 7 materials, the peak current is improved to varying degrees. This can be attributed to the presence of conductive materials, which expands the active specific surface area of the working electrode, allowing more active substances in the electrolyte to participate in the charge transfer. This is an excellent natural condition for the construction of biosensors. It is worth noting that the electrical signal gain of the SPEC electrode deposited with MXene and p-COF is more prominent, reaching 260μA / cm2 and 275μA / cm2 respectively, and the gain efficiency exceeds 55%, which makes it possible for the sensor to have a lower detection limit.
[0086] 1.3 Analysis of reaction kinetics of substrate materials
[0087] Specific surface area is a necessary condition for selecting sensing materials. A large specific surface area can provide more active sites for the binding of biomarkers. Therefore, the adsorption / desorption curves (BET) of MXene and p-COF under N2 were measured. Figure 4 a and 4c, both curves belong to type III isotherms, and the BET values are 5.42m2 / g for MXene and 12.3m2 / g for p-COF, respectively, proving the existence of micropores, and the pore size distribution is concentrated below 5nm and presents a bimodal distribution. The above results show that the two materials have a large specific surface area and can be used for the construction of immunosensors.
[0088] Kinetics is an important indicator for evaluating electrochemical sensors. Faster reaction kinetics is conducive to the transition and dissociation of electrons. In order to further clarify the improvement of this kinetics, such as Figure 5As shown, we obtained the Tafel slopes of these substrate samples by fitting the polarization data (LSV) with the Tafel equation, from which the reaction pathways and rate-determining steps were predicted. The results were consistent with the electrical measurement results. The Tafel diagrams of SPEC, SPEC / MXene@ZnIn2S4, SPEC / ZnIn2S4, SPEC / p-COF, SPEC / COF-v, SPEC / rGO, SPEC / MoS2 and SPEC / MXene were 225, 220, 213, 202, 216, 223 and 218 mV dec-1, respectively. The low Tafel slopes confirmed that MXene and p-COF exhibited high kinetic behavior, which was consistent with expectations. The two materials are not only rich in a variety of groups that are conducive to the binding of biomarkers, but also exhibit excellent electron migration ability, making them excellent choices as biosensors.
[0089] 1.4 Screening of electrochemically active materials
[0090] The above-screened multilayer MXene NSs and p-COF substrate materials have improved the current density and peak current response of the sensor to varying degrees under the premise of adsorbing biomarkers such as antigens, but the effect is not significant enough. In the field of electrochemistry, precious metals are stable as excellent conductors and have been reported to be used as conductive channels to enhance the transition and ionization of electrons, thereby improving the sensitivity of immunosensors. Therefore, we first selected the most common single precious metals Au, Ag, and Pt for in-situ reduction growth on MXene NSs and deposited them on the SPEC surface for current density measurement. It is worth noting that a double oxidation peak appeared near the 0.5V position in the CV curve of the MXene / Pt material, which may be attributed to the "poisoning" of the electrode caused by CO in the electrolyte. Specifically, due to the band gap effect of the Pt base, under the action of the external electric field, it can be understood that a heterojunction is generated at the interface with the MXene substrate. Because the electronic transition ability of MXene is much smaller than that of Pt, uneven charge transfer occurs and it is adsorbed by CO. However, the adsorption energy of carbon monoxide is very strong, and the active sites on the surface of elemental platinum are easily contaminated by carbon monoxide-related intermediates. At the same time, the adsorption of OH* is relatively weak, which makes the dissociation of water on more oxygen-philic sites more difficult. Currently, for platinum nanostructures, alloying by introducing other metals, such as Ag, is an excellent method to improve their electrical properties. Generally speaking, the addition of these metals will lead to a negative shift in the d-band center and a rearrangement of surface atoms, which facilitates the desorption of intermediates and thus has a higher active specific surface area. In addition, platinum-based alloy nanocatalysts accelerate the formation of surface-adsorbed hydroxyl groups (OHads) to DAFCs, promote the removal of toxic intermediates, and improve the utilization efficiency of exposed atoms.
[0091] Subsequently, we used a wet chemical method to prepare MXene / PtAg NPs, MXene / PtAu NPs and MXene / AuAg NPs nanocomposites, and measured their current density differences. MXene / PtAg NPs showed the highest current density. It is worth noting that when Ag was doped into the alloy system, it surpassed the single precious metal Pt. More importantly, the construction of the alloy material eliminated the CO poisoning phenomenon caused by the Pt base; and according to the EIS impedance fitting results of the prepared alloy material and the single precious metal Ag and Pt, the construction of PtAg further reduced the resistance of the material (1.37kΩ), making the transfer and transition of electrons in the sensing material less hindered, which is consistent with the current density measurement results.
[0092] Therefore, the substrate materials that can be used for immunosensors were screened in multiple dimensions, and PtAg alloy structures with different characterizations were constructed. On the one hand, the current density of the sensor was improved, and on the other hand, the CO poisoning phenomenon caused by a single precious metal was solved. On the other hand, the introduction of Ag improved the antibacterial ability of the sensor, which is crucial for the immunosensor platform. Based on electrical measurements, two alloy materials with higher current density, PtAg NPs and PtAg NWs, were selected to sensitize the screened MXene NSs with large specific surface area (multilayer cavities are used to adsorb marker proteins) and p-COF substrate materials with rich surface amino groups and active sites, so as to achieve signal amplification, enhance reaction kinetics, and reduce the electronic transition band gap when constructing the SPEC immunosensor.
[0093] Example 2. Construction of MXene / PtAg sensing platform and performance study of electrochemical immunosensor
[0094] 2.1 Experimental methods
[0095] 2.1.1 Preparation of accordion-structured MXene substrate
[0096] In order to avoid the risk of HF to experimental safety, LiF and hydrochloric acid solution were used as etching solution in this experiment to replace traditional HF acid etching, thereby reducing the experimental risk. The specific experimental steps are as follows:
[0097] (1) Weigh 2 g of LiF material and dissolve it in 20 mL of 12 M HCl solution in a polytetrafluoroethylene beaker and stir at room temperature at 600 rpm for 30 min;
[0098] (2) Weigh 2 g of MAX-Ti3AlC2 and slowly add it to the beaker in the first step, heat and stir to etch, set the temperature to 45 °C, and stir for 24 h to allow the components to react fully, remove the Al layer in the precursor, and form a large number of hydrophilic groups on the two-dimensional surface: -O, -F, -OH, etc.;
[0099] (3) The mixed solution was evenly divided into four centrifuge tubes, and the tubes were repeatedly centrifuged at 3500 rpm in a rotor centrifuge with deionized water for 10 min each time until the pH value of the liquid after centrifugation was neutral;
[0100] (4) The precipitate obtained by the above centrifugation was collected and evenly dispersed in eight centrifuge tubes, placed in a liquid nitrogen environment and quickly cooled to a solid state, and then the target product was dried using a vacuum freeze dryer for 48 hours;
[0101] (5) Take out the product, grind it into powder using an agate mortar and obtain the target product with MXene accordion structure.
[0102] 2.1.2 MXene amination (APTES)
[0103] Based on the negative charge of MXene itself, it will repel precious metals with the same negative charge, affecting their loading process. MXene modified by APTES amino can effectively improve the performance of MXene in antibody detection, improve the sensitivity, selectivity and stability of detection, and provide important technical support for the development of biosensors and diagnostic equipment. Amino modification of MXene surface can regulate its interaction with different biological molecules, making it more selective, helping to reduce the influence of nonspecific adsorption and interfering substances, and improving the accuracy and specificity of detection. At the same time, in order to self-assemble negatively charged PtAg NPs / NWs onto the surface and cavity of negatively charged Ti3C2Tx nanosheets, the dehydration condensation of APTES to modify the Ti3C2Tx surface with amino groups and present a positive charge has become an important part of the construction of immunosensors. The method is as follows:
[0104] First, 10 mg of the above Ti3C2Tx powder was weighed and dissolved in 10 mL of deionized water, 5 mL of anhydrous ethanol was added to the mixed solution, and then 200 μL of APTES solution was added dropwise, and magnetic stirring was performed for 24 hours. After the reaction was completed, the suspension was centrifuged and washed three times at a speed of 3500 rpm to remove the unreacted silane coupling agent, and finally the precipitate was dried in a vacuum oven at 60 ° C overnight to obtain the target product: APTES-MXene powder.
[0105] 2.1.3 Preparation of MXene / PtAg NPs and NWs sensing materials
[0106] Both composite sensing materials were synthesized by self-assembly method, in which PtAg NPs and PtAg NWs were prepared by wet chemical method and solvothermal method using AA and EG as reducing agents, respectively.
[0107] (1) Preparation of MXene / PtAg NPs materials: PtAg NPs used CTAB as a surfactant, H2PtCl6·6H2O and AgNO3 as metal precursors, and AA (ascorbic acid) as a reducing agent to synthesize nanoscale, uniform-sized PtAg nanospheres by a wet chemical method. First, 40 mg of MXene NSs and 30 mg of CTAB were weighed and dissolved in 10 mL of deionized water (DI), and ultrasonically treated until completely dissolved. Then, the prepared H2PtCl6 solution (10 mM, 0.7 mL) and AgNO3 solution (10 mM, 0.3 mL) were dissolved in the above mixed solution, and the mixture was stirred in a 95 °C oil bath for 30 min. Subsequently, AA solution (0.3 M, 1 mL) was quickly injected, and the solution changed from light yellow to dark gray. The mixture was continued to be stirred at 95 °C for 1.5 h, and finally the product was collected by centrifugation (10000 rph), and washed three times with DI water and anhydrous ethanol alternately, and vacuum dried overnight to obtain a uniform MXene / PtAg NPs target product. Among them, different proportions of alloy materials were achieved by adjusting the volume of platinum and silver precursors to achieve the synthesis of PtAg alloy nanoparticles with different atomic ratios; pure platinum and pure silver nanostructures were prepared using a similar method by introducing a single water-soluble H2PtCl6 or AgNO3 as a metal precursor.
[0108] (2) Preparation of MXene / PtAg NWs: PtAg NWs were synthesized by the typical preparation method proposed by Fang et al. In the preparation process, 10 mg of p-COF powder was first weighed and dissolved in ethylene glycol (EG) solution of AgNO3 (0.1 M, 90 μL) and H2PtCl6·6H2O (0.1 M, 210 μL), and then 4 mL of EG and 6 mL of A mixed solution of N,N-dimethylformamide (DMF) was magnetically stirred for 15 minutes until the mixed solution turned light yellow; then weighed KOH (0.4 g) was dissolved in the above mixture, and magnetically stirred at 650 rph for 1 hour until KOH was completely dissolved to form a black-green uniform solution; finally, the mixed solution was transferred to a 40 mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 170 ° C for 4 hours. The product was obtained by centrifugation (1000 rph) and washed three times with deionized water and anhydrous ethanol respectively. The synthesized p-COF / PtAg nanofibers were centrifuged and ultrasonically dispersed in deionized water (5 mL) for later use.
[0109] 2.1.4 Immunosensor Construction (e.g. Figure 6 (shown)
[0110] Taking SPEC / MXene / PtAg NPs as an example, EDC (10 mg / mL) and NHS (10 mg / mL) were added to the prepared cardiac troponin antibody (anti-cTnI, 0.1 mg / mL) solution (PBS), and the solution was placed on a shaker for 15 min to activate the surface carboxyl groups of the antibody. 30 μL of the activated anti-cTnI (Ab) solution was added to the surface of the SPEC / MXene / PtAg NPs electrode, and the reaction was incubated at 37 °C for 1 h. The surface carboxyl groups of anti-cTnI reacted with the surface amino groups of MXene and were fixed to the electrode surface. After the reaction, the electrode was washed with PBS, and 30 μL of 1 mg / mL BSA was added to the surface of the electrode and incubated for 30 min to block the surface active sites and reduce the nonspecific adsorption of the electrode to non-target proteins. Finally, PBS was used to wash away the unbound BSA to obtain the SPEC / MXene / PtAgNPs / Ab / BSA electrode. When testing the cTnI antigen concentration (specific binding), the test solution of different concentrations was added dropwise to the prepared immunosensor surface, incubated for 1 hour, and then rinsed with PBS; the prepared electrode was stored at -4°C and taken out for SPEC test.
[0111] 2.1.5 Test Method
[0112] The electrical performance of the electrode was tested using the Chenhua 660e electrochemical workstation. The specific test items and experimental parameters are as follows:
[0113] (1) Chronoamperometry (It) is a method for recording the curve of current change over time to study electrode performance and stability. The test time is 1000s.
[0114] (2) Square Wave Voltammetry (SWV) is an electrochemical analysis technique. It is a variant of pulse voltammetry. Compared with traditional differential pulse voltammetry, SWV uses square waveform potential pulses instead of simple pulses to better suppress background noise. This square waveform pulse is usually square or nearly square, and usually has a higher pulse frequency than traditional pulse voltammetry. The test range is set to: -0.8V-0.4V.
[0115] (3) Electrochemical Surface Area (ECSA) is usually used to describe the effective surface area of an electrode. In electrochemistry, the active surface area of an electrode is very important for both the surface reaction rate and the apparent rate of the electrochemical reaction. This parameter may be affected by roughness, structure, oxides or other impurities. ECSA can help us better understand the rate of electrochemical reactions, current density and electrode activity.
[0116] (4) Shear surface potential (Zeta potential), which is used to study the interaction between colloids and electrolytes. Since the multi-morphological precious metals designed in this paper are all stabilized by ionic surfactants (CTAB), they have charged properties. Ions with charges opposite to their surface charges (counterions) will be adsorbed to them, while ions with the same charge (common ions) will be repelled. Therefore, the ion concentration near the surface is different from the main concentration in the solution at a certain distance from the surface. The accumulation of counterions close to the surface shields the surface charge, resulting in a decrease in zeta potential. This paper confirms through zeta potential that the presence of a functionalized antifouling coating leads to changes in the electrical properties of the immunosensor surface, thereby adsorbing common clinical protein pollutants to achieve a self-cleaning function.
[0117] The rest of the test conditions are the same as 1.1.2.
[0118] Results and discussion
[0119] 2.2.1 Study on the morphology and structure of accordion-structured MXene substrate materials
[0120] The morphology of MXene materials was analyzed by SEM. Figure 7 As shown in a, its morphology is a multi-layer accordion structure, the multi-layer chambers are clearly visible, and the scale is in the micron order, showing a large specific surface area; XRD was then used to characterize the crystal structure of the etched sample and Ti3AlC2 ( Figure 7 b), it can be seen that after the hybrid etching treatment, the strong peak near 2θ=39° disappears, corresponding to the (104) crystal plane of Ti3AlC2, which proves that the aluminum atoms in Ti3AlC2 have been successfully removed; in addition, compared with the original Ti3AlC2, the (002) diffraction peak of the MXene nanosheets becomes broader and moves to a lower angle, which confirms the increase in the interlayer spacing of the MXene nanosheets, and the results are consistent with the SEM results.
[0121] The chemical state of the MXene substrate was characterized by XPS. The XPS analysis spectrum showed that the MXene nanosheets were mainly composed of Ti, C, O and F elements. No peaks related to the Al element were detected, indicating that the Al layer in the raw material Ti3AlC2 had been completely removed during the etching process. Specifically, Figure 7c shows the spectrum of Ti 2p orbital measurement of MXene after CC peak correction, with peaks concentrated at 453.6, 454.3, 455.3 and 458.6 eV, corresponding to Ti-C, Ti-X, Ti-O and TiO2, respectively. Among them, Ti-X corresponds to titanium carbide or titanium oxide nitride. It can be seen that the Ti element in MXene exists in three different valence states (Ti, Ti2+ and Ti3+). Due to the unstable valence state of Ti, MXene is easily oxidized. In addition, a weaker peak appears at a lower binding energy value, indicating that a small amount of Ti3+ exists in the TiO2 nanoparticles, which is due to the oxygen vacancies on the surface caused by high temperature etching; Figure 7 From the C1s electron orbital of MXene in d, 282.3, 284.8, 286, and 289.4 eV correspond to Ti-C, CC, C-OH, and C=O, respectively. This result further indicates that the surface of MXene nanosheets contains abundant terminal groups, which is conducive to the adsorption of biological proteins such as cTnI, providing an important basis for the construction of immunosensors.
[0122] like Figure 8 As shown in the full spectrum of aXPS, O and F elements were found in the chemically etched MXene nanosheets, indicating that active functional groups were deposited on the surface of the MXene nanosheets during the preparation process. It is worth noting that after loading with PtAg NWs, we can observe that the -F content on the surface of MXene / PtAg NWs is significantly less than that of MXene, which indicates that the CF bond is sensitive to temperature. High-temperature hydrothermal reactions can remove a large amount of -F from the sample surface, making its surface hydrophilic. In general, these results show that Ti3C2Tx nanosheets have high conductivity and rich hydrophilic surface functions. The XRD spectra of MXene and composite materials are shown in Figure 2. Figure 8 As shown in b, the diffraction peak at 2θ = 6.4° is attributed to the (002) plane of the MXene nanosheet. Compared with the XRD pattern of the Ti3Al2C2 MAX phase, there is no characteristic peak at 2θ = 39°, indicating that the product obtained by etching does not contain impurity phase Al elements. After etching, the blue-shifted (002) diffraction peak means the increase in the spacing between the nanosheets. The increase in the interlayer spacing clearly shows that some MXene nanosheets are stacked after etching, confirming the successful preparation of the MXene structure. In addition, the XRD pattern of the composite material shows three strong diffraction peaks at 39.88°, 46.29° and 67.79°, which are located between the peaks of standard Pt (JCPDS card 88-2343) and pure Ag (JCPDScard 04-0783), confirming the successful preparation of MXene / PtAg NPs and MXene / PtAg NWs sensing materials.
[0123] To further explain the synthesis mechanism and surface chemical state of the composites, we evaluated the electrostatic interaction between MXene and PtAg NPs / NWs by measuring the Zeta potential. Fig. 9 a shows that the Zeta potential of MXene aminated with APTES changes from -29mV to +2.51mV. After interacting with APTES, MXene shows a large number of amine groups, making its surface charge tend to be positive. In addition, after the precursor is reduced by wet chemical method (AA) / solvothermal method (ethylene glycol), the Zeta potential of PtAg NPs and PtAg NWs decreases to -16.7mV and -22.5mV, respectively, while MXene / PtAg NPs and MXene / PtAg NWs increase to -7.85mV and -13.2mV, respectively, indicating that PtAg NPs and PtAg NWs are successfully self-assembled on the surface and in the cavity of MXene through electrostatic interactions. In addition, we also used X-ray photoelectron spectroscopy (XPS) to further analyze the surface chemical bonds of MXene / PtAg NWs composites. Fig. 9 (bc) show the Ti2p and C1s orbital spectra of MXene / PtAg NWs, respectively. Figure 7 (cd), an obvious change is that after being loaded with PtAg NWs, the Ti-C bond of the material is significantly weakened, while the Ti-O bond is significantly strengthened. The weakening of the C-Ti bond may indicate that the interaction between carbon and the transition metal is weakened, which may be caused by chemical modification of the surface or surface oxidation reaction. The strengthening of the CO bond may mean that the interaction between oxygen and carbon is enhanced, which may be due to surface oxidation or the presence of more oxygen functional groups. This may affect the conductivity or electrochemical properties of MXene. In addition, since the formation of oxygen vacancies may lead to the strengthening of the bonds between the surrounding carbon atoms and oxygen atoms, the strengthening of the CO bond may reflect the rearrangement or formation of chemical bonds around the oxygen vacancies. Similarly, if the oxygen atom is removed from the MXene structure, the bond between the carbon adjacent to the oxygen atom and the transition metal (Ti) may be weakened because the departure of the oxygen atom will destroy the original bond connection. Therefore, the weakening of the C-Ti bond may reflect the existence or increase of oxygen vacancies, confirming the successful synthesis of the composite material. At the same time, based on the increase of oxygen vacancies, its adsorption mechanism and electron transfer direction are verified, which is consistent with the conclusion of the ZETA potential. Fig. 9As shown in (ef), both the Pt 4f spectrum and the Ag 3d spectrum are decomposed into two spin-orbit components. The binding energies of these four peaks are 71.8eV, 75.1eV, 367.6eV, and 373.6eV, respectively, corresponding to the Pt 4f7 / 2 and Pt 4f5 / 2 orbital peaks of metallic platinum and the Ag 3d5 / 2 and Ag 3d3 / 2 orbital peaks of metallic silver. The obvious Pt 4f and Ag 3d signals in XPS indicate the simultaneous existence of metallic platinum and metallic silver. In particular, compared with the standard Pt0 state, the XPS peak position of Pt 4f shows a positive shift of about 0.6 electron volts. This shift in binding energy is due to the transfer of electrons from Ag to Pt, further confirming the formation of PtAg alloy. In addition, the preparation method (etching method) of MXene used in this embodiment leads to the generation of a large number of oxygen vacancies (Ov) in the substrate material, and PtAg NWs just take advantage of this and accept electrons from the oxygen vacancies of the carrier and have a slight negative charge. Therefore, the modified Pt 4f and Ag3d binding energy in MXene / PtAg NWs is slightly lower than that of pure alloy nanoclusters (0.15–0.35 eV). Fig. 9 (d) The electron paramagnetic resonance (EPR) effectively confirmed this conclusion. It can be clearly observed that each spectrum shows a unique Lorentz line at a magnetic field strength of 3510G, with a g value of 2.003. This feature is attributed to the unpaired electrons confined in the oxygen vacancies. Specifically, MXene nanosheets show a strong Ti3+ spin EPR signal, indicating the presence of oxygen defects. When PtAg NPs and NWs are in situ grown on the surface of MXene nanosheets, the EPR intensity of the two increases to varying degrees compared with MXene nanosheets. This is due to the interface effect of the noble metal, which changes the surface properties, surface charge distribution and reactivity of the MXene substrate, thereby affecting the stability of oxygen vacancies, prompting oxygen atoms to rearrange or reduce their presence on the surface of the MXene substrate. In short, electrons are transferred from vacancies to metals, resulting in the loss of electron-hole pairs bound to oxygen vacancies, causing oxygen atoms to overflow from the lattice, and then increasing oxygen vacancies. Therefore, the abundant oxygen vacancies and oxygen defects in MXene not only help to enhance the electrostatic adsorption of the substrate material and the precious metal, but also the increase in the surface adsorbed oxygen content tends to form more active sites, thereby enhancing the sensing ability. In this embodiment, compared with pure PtAg NWs, the Pt 4f5 / 2 and Pt 4f7 / 2 peaks of the MXene / PtAg NWs composite material move toward lower binding energy, as does the Ag 3d orbital. This may be due to the change in the chemical environment causing electrons to transfer from amine-functionalized MXene to PtAg NWs, thereby allowing the PtAg nanoclusters to gain electrons, resulting in a decrease in binding energy. It is precisely because of the existence of electron transfer that the alloy material and the MXene substrate are tightly bound through electrostatic adsorption.
[0124] In addition, N 1s high-resolution XPS spectra confirmed the presence of amine groups on the surface of APTES-MXene and MXene / PtAg NWs in a protonated state. Fig.10 As shown, the XPS results show that the functionalized N1s orbital has N elements, while the original MXene nanosheets lack them. The two peaks in the APTES / MXene spectrum correspond to free amines with a binding energy of 399.70 eV and protonated amines with a binding energy of 402.24 eV, respectively. When PtAg NWs are electrostatically adsorbed on APTES-MXene, the binding energies become 399.11 eV for free amines and 401.76 eV for protonated amines, respectively. The appearance of the above N1s peaks confirms the successful modification of amine groups on APTES-MXene and MXene / PtAg NWs.
[0125] In order to explore the optimal electrical ratio of PtAg alloy, we configured the two precursors H2PtCl6 and AgNO3 to the same concentration (10mM), and regulated the mass fraction of Pt and Ag in the alloy material by controlling the volume ratio of the two. The parallel experimental ratios were set to Pt:Ag = (1:9), (3:7), (5:5), (7:3) and (9:1). According to the above experimental method, the precursors were reduced by wet chemical method and solvothermal method under the same conditions and in situ grown on the surface and chamber of the MXene substrate, and then deposited on the SPEC electrode for electrical testing. The kinetic test results are shown in Figure 2. Fig.11 As shown in (ab), it is obvious that the TAFEL slopes of Pt7Ag3 NPs and Pt7Ag3 NWs are 151 and 140 mv dec-1, respectively, which are smaller than those of other components. Fig.11 (cd) show the measurement results of cyclic voltammetry (CV) and differential pulse voltammetry (DPV), respectively. Both the current density (CV) and the peak current response (DPV) show a consistent trend of change. When the Pt:Ag ratio is 7:3, the electrical signal is optimally improved compared to the bare SPEC electrode and other ratio conditions, which provides the possibility for the immunosensor to obtain a lower detection limit and higher sensitivity. At the same time, the above measurement results prove the universality of this ratio condition. It is worth noting that when the second precious metal Ag is present, the cyclic voltammetry curve does not show a CO poisoning peak, which meets the prerequisite for the construction of the immunosensor. In addition, in order to further explore the lattice changes of the alloy material and verify the successful doping of different component ratios, we used X-ray diffraction (XRD) spectra to measure the 5-80° XRD spectra under five different ratio conditions, such as Fig.11As shown in (e), the five groups of spectra all showed double strong peaks between the peaks of standard Pt (JCPDS card88-2343) and pure Ag (JCPDS card 04-0783), and all showed the (002), (101) and (105) crystal planes belonging to the MXene substrate, confirming the successful loading of the alloy material. Compared with the standard Pt metal nanocrystals, the diffraction peaks of PtAg nanomaterials shifted to higher angles, but the peak positions were not higher than those of standard Ag nanocrystals. This was due to the incorporation of Ag into the Pt lattice. This peak shift suggested the formation of PtAg alloy nanostructures, which just corresponded to the XPS Pt 4f orbital peak showing a positive shift of about 0.6 eV compared to the standard Pt0 state. This shift in binding energy was due to the transfer of electrons from Ag to Pt, further confirming the formation of PtAg alloys. Among them, the subtle changes in the XRD spectrum, such as Fig.11 As shown in (f), it is not difficult to find that under different doping ratios, the specific alloy peak has a slight shift. In simple terms, with the increase of Pt volume content, the overall peak position has shifted to a higher angle. This is because Ag atoms are larger and Pt atoms are smaller. While keeping the total volume unchanged, the increase of Pt content and the decrease of Ag content lead to lattice contraction, causing the alloy peak position to redshift. This shift once again proves the successful synthesis of multi-ratio alloy materials.
[0126] 2.2.2. Feasibility test and analysis of MXene / PtAg immunosensor construction
[0127] In the process of constructing the SPEC sensor, in order to achieve the best sensing performance, we conducted a 3- / 4- The concentration, antibody (Ab) incubation time and BSA were optimized. 2+ / 3+ Coexistence can act as an electron acceptor to promote the interfacial redox reaction. Therefore, in the SPEC sensor test, adding an appropriate amount of [Fe(CN)6] 3- / 4- It is a commonly used strategy for sensor signal amplification.
[0128] Fig.12 In (a), it can be found that the addition of [Fe(CN)6] 3- / 4- After that, the peak current of the system increases significantly, but when [Fe(CN)6] 3- / 4- When the concentration exceeds 5 mM, the current begins to decrease. This is due to the Fe 2+ / 3+ The coexistence of [Fe(CN)6] as a medium for redox reactions promotes electron transfer at the interface, which is beneficial to the improvement of the current signal. However, the excess [Fe(CN)6] 3- / 4-It will increase the mass transfer resistance on the electrode surface, leading to electrode polarization, that is, the formation of irreversible reaction products on the electrode surface, thereby reducing the response rate and efficiency of the electrode, which will reduce the sensitivity of the electrochemical test. In addition, high concentrations of [Fe(CN)6] 3- / 4- It will increase the viscosity of the electrolyte, thereby increasing the diffusion resistance in the electrochemical test. This may lead to the restriction of reaction kinetics and mass transfer process, affecting the accuracy and sensitivity of the test. 3- / 4- With the increase of concentration, the current of SPEC / MXene / PtAg NWs reaches the maximum value and then gradually decreases. 3- / 4- The signal amplification effect is most obvious when the concentration is 5mM. Therefore, 5mM [Fe(CN)6] 3- / 4- It is conducive to obtaining the best current density. Furthermore, the incubation time of Ab and BSA will also affect the current, mainly affecting the antibody fixation density. Fig.12 In (b) and (c), as the incubation time of Ab and BSA increases, the peak current decreases first and then stabilizes. This platform indicates that the number of biomolecules adsorbed on the electrode / solution interface has reached saturation. Therefore, the incubation time of Ab and BSA on the electrode was set to 80 min and 50 min, respectively, to achieve the optimal parameters of the immunosensor.
[0129] During the sensor construction process, Fig.13 (a) Recorded the immunosensor in the presence of 5 mM NaCl2 and 5 mM [Fe(CN)6] 3- / 4- The peak current intensity of the SPEC / MXene / PtAg NWs electrode (F) is about 450 mA / cm 2 , which is higher than 235mA / cm of the bare SPEC electrode (B). 2 and 305 mA / cm for SPEC / MXene electrode (F) 2 The increased current density indicates that the MXene composite material sensitized by PtAg NWs can effectively improve the electrochemical activity of the sensor. After the electrode was incubated with antibody Ab (H) and BSA (J), the peak current gradually decreased to 415 mA / cm 2 and 403mA / cm 2 This decrease is due to the steric hindrance effect of non-conductive Ab and BSA, which will hinder the interfacial transfer rate of charge carriers at the electrode / electrolyte interface. Finally, after modification with 100 ng / mL cTnI antigen Ag(L), the peak current was further reduced to 200 mA / cm 2, which is attributed to the formation of immune complexes. To further confirm the above process, electrochemical impedance spectroscopy (EIS) was used to measure the sensor at each assembly stage, and the charge transfer resistance (Rct) fitting curve at the electrode / electrolyte interface is shown in Fig.13 As shown in (b), the Nyquist plot shows that the Rct of the electrode (F) is only 0.62 kΩ, which is much smaller than the Rct of the bare SPEC electrode 7.3 kΩ (B). After the electrode is modified with Ab (2.7 kΩ, H), BSA (4.6 kΩ, J) and Ag (7.9 kΩ, L), the Rct gradually increases. This is because non-conductive proteins and immune complexes block the interfacial electron transfer path. The above results confirm the feasibility of the developed immunosensor for cTnI detection.
[0130] 2.2.3 Detection performance of MXene / PtAg immunosensor
[0131] Stability and reproducibility are important factors in evaluating sensor performance. Fig.14 (ab) show the multi-cycle CV test curves of MXene / PtAg NPs and NWs materials in the -1V-1V range on the SPEC electrode. According to the degree of curve fit, it can be seen that during the 10 consecutive scans, the above-constructed immunosensor has almost no current density loss and still maintains more than 98% of the initial value. The results show that both sensors have excellent current stability. In order to examine its reproducibility, the two sensors were tested on multiple electrodes under the same conditions. The DPV peak current response is shown in Figure 2. Fig.14 As shown in (cd), the calculated relative standard deviations (RSDs) are small, namely 3.68% and 2.46%, respectively, indicating that the prepared immunosensors exhibit good reproducibility, which can be attributed to the uniformity of the precious metal alloy materials.
[0132] In order to further obtain the clinical detection capabilities of the two sensors, including their sensitivity, detection limit, specificity and current attenuation, we evaluated the sensing performance of the SPEC immunosensor by establishing a functional relationship between current density and cTnI concentration in PBS solution. First, the SPEC / MXene / PtAg NPs immunosensor was analyzed. Fig.15 As shown in (a), as the antigen concentration gradually increases, the peak current response continues to decrease. The fitting calculation found that there is a certain correlation between the cTnI concentration and the change of the current peak signal, such as Fig.15(b) shows that when the cTnI concentration is controlled within the range of 1pg / mL to 1μg / mL, I (I represents the current density after the action of cTnI) is linearly correlated with the logarithm of the cTnI concentration (lgCcTnI). The linear equation is I = -28.96lgCcTnI + 0.87, and R2 is 0.99 (N = 10). The lower limit of detection (LOD) is 0.11pg / mL (S / N = 3).
[0133] Similarly, if Fig.16 As shown in (a), as the antigen concentration gradually increases, the peak current response of the SPEC / MXene / PtAg NWs sensor continues to decrease. Fig.16 (b) shows the logarithmic relationship between (I0-I) / I0 and cTnI concentration within the same cTnI gradient concentration range of 1pg / mL to 1μg / mL. After fitting, it is still linearly correlated, with smaller errors and exponentially increased sensitivity. The linear equation is I = -57.61lgCcTnI + 1.63, R2 is 0.99 (N = 10), and the detection limit (LOD) is reduced to 0.093pg / mL (S / N = 3). Obviously, the cTnI immunosensor based on the PtAg NWs doped sensitized structure has a higher clinical applicability than SPEC / MXene / PtAg NPs, which is due to the presence of alloy nanobeams, which act as a flow channel to enhance the transfer and transition ability of interface electrons, thereby enabling the sensor to recognize smaller immune complexes.
[0134] Specificity and current density loss efficiency (anti-fouling) are also important factors affecting the clinical use of sensors. Therefore, under the same experimental conditions, we continued to use non-specific antigens such as myoglobin, N-terminal B-type natriuretic peptide pro (NT-Pro-BNP), creatine kinase BB antigen (CK-BB), procalcitonin (PCT), and common molecules in human serum such as glucose, ascorbic acid, glutathione, lactate, dopamine, and uric acid to evaluate the specificity and anti-interference ability of the two immunosensors. Fig.15As shown in (c), the critical value for clinical diagnosis of myocardial infarction is usually cTnI: 0.5μg / L, so we set the detection concentration of cTnI to 0.1ng / mL, and the concentration of all other interferents is 10ng / mL. By calculating the current density loss efficiency, it can be seen that the effect of interferents on the peak current can be ignored. This result shows that the two immunosensors developed have good specificity and anti-interference ability. Further, in order to explore the storage stability of the above two immunosensors. After the sensor was stored at room temperature (20℃) for 8 days, the current density can reach more than 90% of the initial value. It can be seen that the SPEC immunosensor based on MXene / PtAg NPs and MXene / PtAg NWs has excellent sensing performance such as high sensitivity, good stability and strong anti-interference ability.
[0135] 2.2.4. MXene / PtAg charge transfer mechanism and kinetic analysis
[0136] Fig.17 (ad) show the bare SPEC electrode, SPEC / MXene, SPEC / MXene / PtAg NPs, and SPEC / MXene / PtAg NWs sensors in 5 mM [Fe(CN)6] 3- / 4- The CV scan curve under the environment, the scan rate range is set to 100 to 600mV s-1, and the first peak at about 0.4V indicates the loss of the first electron, that is, the completion of the oxidation reaction. As the scan rate increases, the electrons rearrange to form free radical oxygen species. Subsequently, the reaction proceeds through entropy-driven free radical splitting reactions, involving another electron loss, which ultimately intensifies the oxidation reaction. It is worth noting that after the noble metal is loaded, the reduction peak moves significantly to a higher energy level, proving that the sensor has obtained a high-energy-level electron, and high-energy-level electrons are more likely to transition, which is consistent with kinetic theory. Fig.17 (e) shows the band error fitting of the oxidation peak current (Ipa) and the scan rate. The results all show a good linear relationship, which indicates that the electrochemical oxidation on the sensor is a surface-mediated process. According to the Randles-Sevick equation, the slope of the linear equation can reflect the active specific surface area of the electrode. It can be seen that as the sensing material is built layer by layer, the ECSA gradually increases to 0.179 and 0.223, which is much higher than the bare SPEC electrode (0.052) and SPEC / MXene sensor (0.115). It improves the reaction kinetics and also provides more active sites and higher active specific surface area for the adsorption of antigens and antibodies; further, the above process is verified by EIS impedance spectroscopy, such as Fig.17As shown in (f), the fitting curve clearly shows that with the layer-by-layer construction of MXene substrate and PtAg NPs and NWs, the synergistic gain effect of the two becomes more and more obvious, and the resistance value decreases from 7.3kΩ of the bare SPEC electrode to 0.62kΩ. The above shows that the construction of the immunosensor drastically reduces the energy required for electron transition, making it easier for electrons to transfer to the conduction band. When the higher peak current response matches the target detection object with lower concentration, the detection limit and sensitivity of the immunosensor can be doubled.
[0137] 2.2.5 MXene / PtAg NWs clinical serum sample detection
[0138] The SPEC / MXene / PtAg NWs immunosensor constructed above showed excellent detection potential. We then performed actual measurements on real serum samples. The clinical serum samples came from the Department of Critical Care Medicine, Shanghai Chest Hospital. In order to minimize the impact of experimental variables on the measurement results, we used PBS buffer to dilute the single sample to different degrees, thereby obtaining serum samples with a gradient effect, such as Fig.18 As shown in (a), the electrode still plays a role in identifying immune markers in serum, and the peak current shows an obvious gradient change. It is worth noting that, unlike the direct measurement of purified cTnI, the addition of serum directly leads to partial current loss. This may be due to the increase in contaminating proteins in the complex serum environment, which leads to electrode polarization. Fig.18 (b) shows the error current values under different serum concentrations. Through linear fitting, it was found that the linear detection range of the sensor was 0.13 ng / mL-0.325 ng / mL, and the overall cubic polynomial fitting equation was I=152.8-42.9X+84.7X2-80.5X3, R2 was 0.97 (N=8), and the detection limit (LOD) was 0.13 ng / mL (S / N=3), which also met the requirements for defining the critical value of cTnI in actual measurement.
[0139] Example 3. Construction of p-COF / PtAg sensing platform and performance study of electrochemical immunosensor
[0140] 3.1 Experimental methods
[0141] 3.1.1p-COF synthesis
[0142]
[0143] 16.7 mg TAPP (7.5 μmol) and 10 mg TA (15 μmol) were mixed and introduced into a 20 ml SCHLENK tube. Then, 7 mL o-dichlorobenzene and 3 mL n-butanol mixed solvent were injected into the reaction tube. Ultrasonication was performed for 10 min to completely dissolve the mixture. Then, 800 μL acetic acid (12 M) was slowly dripped in as a catalyst. The reaction tube was evacuated by liquid nitrogen cooling to remove bubbles. After three cycles of cooling, the mixture was brought to room temperature. After that, the mixture was placed in a vacuum drying oven at 120 ° C and heated for 72 h to perform esterification reaction. After the reaction was completed, it was cooled to room temperature. Then, the mixture was collected by centrifugation, soaked and washed three times with tetrahydrofuran (THF) and N, N-dimethylformamide (DMF), and finally dried in a vacuum oven at 60 ° C for 12 h to obtain a magnetic green-brown solid product. After grinding, the p-COF powder target product was obtained. It is worth noting that p-COF powder needs to be dispersed by high-intensity ultrasonication before use.
[0144] 3.1.2 Preparation of p-COF / PtAg sensing materials
[0145] (1) Preparation of p-COF / PtAg NPs: Nanoscale PtAg nanospheres with uniform particle size were synthesized by wet chemical method using CTAB as surfactant, H2PtCl6·6H2O and AgNO3 as metal precursors, and AA as reducing agent. First, 20 mg of p-COF powder and 30 mg of CTAB were weighed and dissolved in 10 mL of deionized water (DI) and ultrasonically treated until completely dissolved. Then, the prepared H2PtCl6 solution (10 mM, 0.7 mL) and AgNO3 solution (10 mM, 0.3 mL) were dissolved in the above mixed solution. The mixture was stirred in a 95°C oil bath for 30 min. Subsequently, AA solution (0.3 M, 1 mL) was quickly injected. At this time, the solution changed from light yellow to dark gray. The mixture was continued to be stirred at 95°C for 1.5 h. Finally, the product was collected by centrifugation (10000 rph), and washed three times with DI water and anhydrous ethanol alternately. The uniform p-COF / PtAgNPs target product was obtained by vacuum drying overnight.
[0146] (2) Preparation of p-COF / PtAg NWs: During the preparation of PtAg NWs, 10 mg p-COF powder was dissolved in an ethylene glycol (EG) solution of AgNO3 (0.1M, 90μL) and H2PtCl6·6H2O (0.1M, 210μL), and a mixed solution of 4mL EG and 6mL N,N-dimethylformamide (DMF) was added, and magnetic stirring was performed for 15min until the mixed solution turned light yellow; then, a weighed amount of KOH (0.4g) was dissolved in the above mixture, and magnetic stirring was performed at 650rph for 1 hour until KOH was completely dissolved to form a black-green uniform solution; finally, the mixed solution was transferred to a 40mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 170℃ for 4 hours. The product was obtained by centrifugation (1000rph) and washed three times with deionized water and anhydrous ethanol respectively. The synthesized p-COF / PtAg nanofibers were centrifuged and ultrasonically dispersed in deionized water (5mL) for later use.
[0147] 3.1.3 Construction of p-COF / PtAg immunosensor
[0148] First, the anti-cTnI (Ab) solution was mixed with a coupling reagent containing EDC (20 mM) and NHS (10 mM), and placed on a shaker for 15 min to activate the carboxyl groups in the Ab. 30 μL of the activated Ab (0.1 mg / mL) solution was introduced into the SPEC / p-COF / PtAg electrode surface and incubated at room temperature for 1 h. After careful rinsing with PBS, 30 μL of BSA (1 mM) solution was added and incubated for 30 min to block nonspecific active sites and nonspecific adsorption. After flushing away the unbound BSA with PBS, the constructed sensor can be stored in an environment of 4°C.
[0149] When testing, cTnI (Ag) solutions of different concentrations were placed on the electrode surface where the sensing material had been deposited and incubated at room temperature for 1 hour. After the target cTnI was specifically immune-recognized, the electrode was washed with PBS and the SPEC test was performed. The formation of immune complexes on the sensing interface can increase the electron transfer resistance of the prepared electrode, resulting in a significant decrease in the electrode current density. This signal change was eventually recorded and used to quantify the amount of cTnI. The construction of the SPEC / p-COF / PtAg / Ab / BSA electrochemical immunosensor is shown in the figure.
[0150] 3.1.4 Test method is the same as in Example 2
[0151] Results and discussion
[0152] 3.2.1p-COF synthesis and characterization studies
[0153] FT-IR, XRD and XPS were used to study the chemical properties and structure of the materials. Fig.19 In (a), the FT-IR spectra of TAPP, TA and p-COF show that the absorption band in TA is located at 1693 cm-1, which corresponds to the characteristic vibration of the aldehyde C=O bond, and the absorption band in TAPP is located at 965 cm-1 and 803 cm-1, which corresponds to the stretching vibration of the NH bond. For p-COF, a new absorption peak at 1602 cm-1 is observed in the FT-IR spectrum, which corresponds to the stretching vibration of the C=N bond, indicating the existence of the imine bond in p-COF, confirming the successful formation of the imine bond between TAPP and TA based on the Schiff base reaction, i.e., the formation of p-COF. In addition, the C=O vibration bond (1693 cm-1) and the stretching vibration bond (3300-3500 cm-1) almost completely disappeared, further confirming the structural integrity of p-COF.
[0154] To further confirm the successful preparation of p-COF, P-COF / NPs and NWs, the crystal structures of the three materials were measured by X-ray diffraction (XRD). Fig.19 As shown in (b), specifically, the strong peaks with 2θ of 4.30°, 8.58° and 11.31° were assigned to the (200), (400) and (510) crystal planes of p-COF, which are consistent with previous reports and belong to the P6_ space group, confirming the successful preparation of p-COF and composite materials. The broad diffraction peak at 2θ = 13.96° was attributed to the conjugated stacking of π-π bonds, because after the introduction of nonlinear pyridine ligands, the planar structure of p-COF was distorted due to the nonlinear connection between the aldehyde group and the porphyrin node. Specifically, the central triphenyl nucleus of TAPP is not in the same plane, resulting in a significant distortion of the connected porphyrin ring, which weakens the π-π stacking interaction.
[0155] 3.2.2 Morphology, structure characterization and loading mechanism analysis of p-COF / PtAg composite nanomaterials
[0156] The structures of p-COF / PtAg NPs and p-COF / PtAg NWs were characterized by SEM, TEM, HRTEM and SAED. Fig. 20 As shown in (a) and (b), all p-COF crystals are spherical structures, and the spherical covalent organic framework particles are tightly stacked with each other, without obvious cracks or defects, and the diameter is controlled at about 70nm; Fig. 20 The SEM and TEM images in (ce) clearly show the structure of p-COF and PtAg NWs loading, and the HRTEM image further verifies the nanowire characteristics, with the diameter of each nanofiber measured to be only 1.9 ± 0.2 nm ( Fig. 20f), in addition, HRTEM images show the crystalline nature of these NWs, with a lattice spacing of 0.226nm, corresponding to the (111) plane (face-centered cubic, fcc), located between the Pt (111) (0.229nm) and Ag (111) (0.2046nm) planes, and the lattice spacing belonging to p-COF (d = 0.345), and the simultaneous appearance of the lattice spacing confirms the successful preparation of the p-COF / PtAgNWs composite material. In addition, SAED confirms the single crystal structure of the material ( Fig. 20 f). Similarly, the SEM and TEM images of p-COF / PtAgNPs clearly show the uniform loading structure of the material. The morphology of the covalent organic framework does not change significantly after loading, and the particles are still tightly stacked with each other without obvious cracks or defects ( Fig. 20 gi), demonstrating the successful preparation of the material.
[0157] Similarly, to further explain the synthesis mechanism of the composite material, we evaluated the electrostatic interaction between p-COF and PtAg NPs / NWs by measuring the Zeta potential. It is worth noting that, unlike MXene, the synthesis of p-COF is through vacuum esterification condensation, and TAPP as one of the monomers is rich in amino groups, which makes p-COF itself positively charged, eliminating the amination step, which also provides great advantages for the subsequent construction of immunosensors, such as Fig.21 As shown in (a), its initial Zeta potential is 15.7mV. After PtAg NPs and PtAg NWs are loaded, the Zeta potentials of MXene / PtAg NPs and MXene / PtAgNWs increase from -16.7mV and -22.5mV of pure noble metals to -2.9mV and -5.2mV, respectively, indicating that PtAg NPs and PtAg NWs are successfully self-assembled on the p-COF surface through electrostatic interactions. In addition, we also used X-ray photoelectron spectroscopy (XPS) to further analyze the surface chemical bonds of the p-COF / PtAg NWs composite material. Fig.21 (b) shows the high-resolution XPS spectrum of the N1s orbital, which confirms that when p-COF is bound to PtAg NWs, amine groups exist on the surface of p-COF / PtAg NWs and exist in a protonated state. There are two peaks in the spectrum, corresponding to free amines with a binding energy of 399.30 eV and protonated amines with a binding energy of 401.24 eV. The appearance of the above N1s peaks confirms the existence of amine groups on p-COF / PtAg NWs. Further, as Fig.21As shown in (ef), both the Pt 4f orbital spectrum and the Ag 3d orbital spectrum are decomposed into two spin-orbit components. The binding energies of these four peaks are 71.2 eV, 74.8 eV, 367.6 eV, and 373.6 eV, corresponding to the Pt 4f7 / 2 and Pt 4f5 / 2 orbital peaks of metallic platinum and the Ag 3d5 / 2 and Ag 3d3 / 2 orbital peaks of metallic silver, respectively. The obvious Pt 4f and Ag 3d signals in XPS indicate the simultaneous existence of metallic platinum and metallic silver. In addition, another important monomer based on p-COF is terephthalaldehyde (TA). The presence of a large number of aldehyde groups and high temperature conditions lead to the generation of a large number of oxygen vacancies (Ov) in the substrate material. PtAg NWs just take advantage of this advantage and accept electrons from the oxygen vacancies of the carrier and have a slight negative charge. Therefore, the modified Pt 4f and Ag 3d binding energy in MXene / PtAg NWs is slightly lower than that of pure alloy nanoclusters (0.15–0.32 eV). This is also due to the interface effect of the precious metal, which changes the surface properties, surface charge distribution and reaction activity of the p-COF substrate, thereby affecting the stability of oxygen vacancies and prompting oxygen atoms to rearrange or reduce their presence on the surface of the p-COF substrate. Therefore, the abundant oxygen vacancies and oxygen defects in p-COF help to enhance the electrostatic adsorption of the substrate material and the precious metal. In this study, compared with pure PtAg NWs, the Pt 4f5 / 2 and Pt 4f7 / 2 peaks of the p-COF and PtAg NPs / NWs composites moved toward lower binding energy, and the Ag 3d orbital showed the same trend of change. This may be due to the change in the chemical environment, which caused the electrons to transfer from p-COF to PtAg NWs, so that the PtAg nanoclusters gained electrons, resulting in a decrease in binding energy. It is also because of the existence of electron transfer that the alloy material and the p-COF substrate are closely combined through electrostatic adsorption.
[0158] 3.2.3 Feasibility test and analysis of p-COF / PtAg immunosensor construction
[0159] The sensor construction parameter settings are the same as those in Example 2. During the sensor construction process, Fig. 22 (a) Recorded the immunosensor in the presence of 5 mM NaCl2 and 5 mM [Fe(CN)6] 3- / 4-The current density changes in PBS electrolyte. The peak current intensity of the SPEC electrode (i) is 235mA / cm2, and the peak current intensities of the SPEC / p-COF electrode (ii) and the SPEC / p-COF / PtAg NWs electrode (iii) are 360mA / cm2 and 607mA / cm2, respectively. The increase in current density indicates that the constructed PtAg NWs loaded covalent organic framework structure effectively increases the active specific surface area of the electrode. After modification with antibody Ab (iv) and BSA (v), the photocurrent gradually decreases to 503mA / cm2 and 375mA / cm2, respectively. This change is the same as the trend of the sensor in the previous chapter. After incubating 100ng / mL of cTnI antigen Ag (vi) on the electrode, the photocurrent further decreases to 204mA / cm2, which is also attributed to the formation of immune complexes. In order to further verify the above microscopic process, electrochemical impedance spectroscopy (EIS) was used to measure the sensor at each assembly stage, and the charge transfer resistance (Rct) fitting curve at the electrode / electrolyte interface was as follows: Fig. 22 As shown in (b), the Nyquist plot shows that the fitted Rct shows a change trend consistent with the current density. Among them, the Rct of the bare SPEC electrode is 7.2kΩ(i), the Rct of the SPEC / p-COF electrode(ii) is 2.8kΩ, and the Rct of the substrate material modified by PtAg NWs is further reduced to 0.46kΩ(iii). After Ab (1.53kΩ, iv), BSA (2.4kΩ, v) and Ag (7.6kΩ, vi) are incubated on the electrode in sequence, Rct gradually increases. Obviously, the SPEC electrode modified by p-COF / PtAg NWs reduces the interfacial charge transfer resistance by several times, indicating that the presence of alloy nanoclusters as high-quality conduction channels sharply reduces the energy required for electron transition, thereby allowing the carriers to transfer rapidly at the electrode / electrolyte interface, while the generation of non-conductive immune complex proteins inhibits the interfacial electron transfer process. The above results all indicate that the immunosensor constructed based on SPEC / p-COF / PtAg NWs has certain clinical feasibility for cTnI detection.
[0160] 2.3.4 Detection performance of p-COF / PtAg immunosensor
[0161] Stability and reproducibility are important factors in evaluating sensor performance. Fig.23 (a) shows the sustained current response (It) of the electrode within 1000 s. The current has no obvious fluctuation (<3%). The good stability can be attributed to the chemical stability of the p-COF structure. The clustered PtAg NWs act as a conductive channel for electrons, which has a higher current density than PtAg NPs ( Fig.23b) To investigate its reproducibility, the current response of 7 electrodes was measured under the same conditions. Fig.23 (cd) It can be seen that the relative standard deviation (RSD) is less than 1.13%, indicating that the prepared electrodes have good reproducibility and precision.
[0162] The sensing performance of the SPEC / p-COF / PtAg NPs immunosensor was evaluated by the relationship between the peak current and the cTnI concentration in PBS solution. Fig.24 As shown in (a), as the antigen concentration gradually increases, the current signal gradually decreases; after adding 1 μg / mL cTnI antigen solution, the current density decreases to 70 mA / cm2. Fig.24 (b) The linear fitting relationship between the standard error and the actual current value after measurement of multiple groups of electrodes is shown. In the range of 1pg / mL to 1μg / mL, the results show an excellent linear correlation with an R2 of 0.98 (N=8), the linear equation is I=-61.55lgCcTnI+3.08, and the detection limit (LOD) is 0.069pg / mL (S / N=3). Compared with the immunosensor constructed based on SPEC / MXene, its detection limit and sensitivity (61.55) have been doubled improved while ensuring the linear relationship.
[0163] Similarly, for the SPEC / p-COF / PtAg NWs immunosensor, e.g. Fig.25 As shown in (a), in the detection range of 1pg / mL to 1μg / mL, as the antigen concentration increases, the immune complex protein hinders the transition of electrons, thus requiring more energy, causing the peak current density to decrease in a gradient manner. Fig.25 (b) shows the error-free linear fitting curve of the actual measured current density value. The results also show a strong linear relationship with R2 of 0.98 (N = 8), a sensitivity as high as 67.56, a linear equation of I = -67.56lgCcTnI + 2.65, and a detection limit (LOD) of 0.04pg / mL (S / N = 3), which meets the needs of clinical diagnosis of AMI. In order to evaluate the comprehensive level of the sensor in multiple dimensions, we investigated the current cTnI detection methods with relatively excellent performance and related parameters such as detection limit and sensitivity. Compared with the previously reported detection methods, the two SPEC immunosensors constructed in this chapter have a wider linear detection range, lower detection limit, and higher sensitivity, as shown in Table 1.
[0164] Table 1 Detection limits of different cTnI detection methods
[0165]
[0166] Under the same experimental conditions, the specificity and anti-interference ability of the immunosensor were evaluated by detecting nonspecific antigens such as myoglobin, N-terminal pro-B-type natriuretic peptide (NT-Pro-BNP), creatine kinase BB antigen (CK-BB), procalcitonin (PCT), and common molecules in human serum such as glucose, ascorbic acid, glutathione, lactate, dopamine, and uric acid. Fig.24 As shown in (c), compared with the addition of 0.01 ng / mL of cTnI, the effect of all interferences (all at a concentration of 10 ng / mL) on the current is negligible. This result shows that the developed immunosensor has good specificity and anti-interference ability. Fig.24 (d) The storage stability of the immunosensor was studied. After the sensor was stored at 20°C for 2 weeks, the current intensity reached more than 93% of the initial value. It can be seen that the two constructed SPEC immunosensors based on p-COF / PtAg loading have excellent sensing performance such as high sensitivity, good stability, and strong anti-interference ability.
[0167] 2.2.5. Clinical serum sample testing
[0168] Based on the low detection limit of the currently constructed immunosensor, in order to be closer to clinical use, we further studied the detection of cTnI concentration in clinical serum. We selected a group of patient serum samples from Shanghai Chest Hospital. The cTnI concentration in the serum was determined to be 13.77 ng / mL after clinical testing. We then diluted the serum with PBS solution, with the gradient set to 1X, 5X, 10X, 40X, 80X, and 100X. Subsequently, the SPEC / p-COF / PtAg NWs immunosensor incubated with cTnI antibody was used for actual measurement. The peak current change was as follows: Fig.26 As shown in (a), the results show that the current changes are consistent with the expected ones, and the changes are relatively uniform. Fig.26 (b) shows the relationship between the standard error and linear fitting of multiple groups of electrode tests. The results also show a strong linear relationship of R2=0.94, and the linear equation is I=-50.11lgCcTnI+6.03, which proves that it is linearly correlated in the range of 1μg / mL to 1pg / mL, and the detection limit is 0.093pg / mL, which is lower than the critical value of clinical detection.
[0169] We then evaluated the clinical applicability of the SPEC / p-COF / PtAgNWs immunosensor by measuring the cTnI in the above clinical serum samples. We summarized and compared the test results with the cTnI concentration obtained by the currently accepted commercial ELISA method, and the measurement results are shown in Table 2. The relative deviation (RSD) of the cTnI concentration determined by the SPEC immunosensor ranged from 0.06 to 0.17% (n=3), and the recovery rate ranged from 96 to 109.5%, indicating that the immunosensor showed good potential for detecting cTnI in serum samples. When testing clinical serum samples, with a threshold of 0.03 ng / mL, sample 1 was negative compared with the blood samples of healthy blood donors, and the difference was not significant (P>0.05), and samples 2-6 were positive compared with the blood samples of healthy blood donors, and the difference was significant (P<0.05). The results demonstrated the high feasibility of the prepared SPEC sensor for analyzing cTnI in blood samples of patients and healthy blood donors.
[0170] Table 2 Clinical serum cTnI determination
[0171]
[0172] 2.2.6. microRNA-133a detection
[0173] In this embodiment, the titration method is selected to modify multiple electrodes simultaneously to minimize the error caused by variables. In order to customize the area of the working electrode, 8 μL of p-COF / PtAg NWs solution is titrated on the working electrode, and after drying at 75°C using a constant temperature heating stage, the customized anti-microRNA-133a DNA sequence probe is attached to the surface of the SPEC working electrode deposited with p-COF / PtAg NWs. The probe is customized with C6-SH at the "5'-" end (allowing covalent binding with PtAg NWs) and methylene blue (MB) at the "3'-" end (allowing electron transfer on the electrode).
[0174] like Fig. 27As shown, the specific steps are as follows: the first step is to reduce 100 μM anti-microRNA-133a DNA probe in 50 mM phosphate buffer (pH = 7, containing 1 M NaCl and 10 mM MgCl2) for 1 hour in the presence of 10 mM tris (2-carboxyethyl) phosphate hydrochloride (TCEP-HCl), wherein TCEP-HCl is indispensable in order to reduce the disulfide bonds in the probe before covalently binding to PtAg NWs to make the sulfhydryl molecules more stable. In the second step, 20 μL of the probe was titrated in the working electrode area for 1 hour in a humid chamber (37°C oven) at room temperature, and the unbound probe was rinsed with DEPC water. Subsequently, the microRNA-133a to be tested was extracted by centrifugation and dissolved and diluted to the selected concentration (nM-fM) in a DEPC environment to be fixed on the SPEC / p-COF / PtAg NWs. After incubation at 30°C for 30 minutes, the SPEC working electrode was gently washed with deionized water and continued to be incubated in a 37°C oven containing 2mM thiol-1-hexanol for 1.5 hours to protect the vacancies on the working electrode. Finally, the unbound thiol groups on the SPEC were rinsed off with deionized water, and multi-electrode gradient measurement was performed in a PBS buffer solution environment.
[0175] like Fig.28 As shown in (a), after incubation with different concentrations of microRNA-133a aptamers, the immunosensor showed different peak current responses. As the concentration of microRNA-133a gradually increased to the μM level, the current density decreased successively. Similar to cTnI, microRNA and the probe complementarily bound to form an immune complex, which produced a blocking effect and hindered the electron transfer process
[97] . Fig.28 (b) shows the linear relationship of peak current and error bar analysis after multi-electrode gradient measurement. The results show that there is a linear correlation in the concentration range of 0.1fM-1μM, R2 is 0.97 (N=8), the linear equation is I=-52lgCmicroRNA-133a+2.82, and the detection limit (LOD) is as low as 0.049fM (S / N=3). It meets the critical value of clinical detection, further improves the clinical universality of the immunosensor, provides the possibility for multi-channel detection of the immune platform, and greatly reduces the occurrence of false positive cases.
[0176] Then, if Fig.29As shown in (a), the patient serum from Shanghai Chest Hospital was diluted 5X-100X. After incubating with different concentrations of patient serum, the immunosensor also showed differences in peak current response. As the serum concentration decreased, the current density decreased. Similar to cTnI, microRNA and the probe complementarily bound to produce immune complexes, resulting in a blocking effect and hindering the electron transfer process. Fig.29 (b) shows the linear relationship of peak current and error bar analysis after multi-electrode gradient measurement. The results show that it is linearly correlated in the concentration range of 5fM-10nM, R2 is 0.99 (N=8), the linear equation is I=-40.57lgCmicroRNA-133a+1.74, and the detection limit (LOD) is as low as 0.076fM (S / N=3). It also meets the critical value of clinical detection, proving that the immunosensor can be used for rapid diagnosis and early monitoring of clinical assistance.
[0177] Example 4. Construction and performance study of immunosensor antifouling coating
[0178] Through the above experiments, it was found that compared with microRNA-133a in the PBS environment, the linear detection range of the sensor decreased due to the complexity and diversity of patient serum. The presence of serum pollutants weakened the electrode's ability to discriminate immune complexes formed by complementary base pairs, and the electrode showed indiscriminate current density, resulting in performance loss. Therefore, constructing an anti-fouling coating material with self-cleaning function is a necessary condition to further improve the sensor sensitivity and linear detection range.
[0179] In this example, a novel, bifunctional antifouling coating (CQDs@PDA) was prepared by forming covalent boron ester bonds between the o-diphenol groups in polydopamine and ionic and cationic polymers with benzooxyborane side chains. To incorporate antifouling properties into the coating and enhance its biocompatibility, the bioinspired ionic compound 2-methacryloyloxyethyl phosphorylcholine (MPC) was selected, and an ionic polymer poly(MPC-st-MAABO) (MAABO: 5-methacrylamide-1,2-benzooxyborane) containing benzooxyborane side chains was synthesized. In addition, to impart antibacterial properties to the surface, a cationic polymer poly(2-(methacryloyloxy)ethyltrimethylammonium (META)-st-MAABO) containing quaternary ammonium groups was synthesized. These synthetic polymers were covalently grafted to the surface by forming a robust cyclic boron ester complex with the o-diphenol groups on the surface of the polydopamine (PDA) coating, endowing the surface with the property of contact killing of specific proteins by bacteria. After adding a competing molecule (sugar) containing cis-diol, the boron ester complex formed by the ortho-diphenol group of PDA was displaced and the attached polymer layer was peeled off from the surface, resulting in the release of adsorbed proteins and bacteria electrostatically attached to the polymer layer. In addition, the addition of CQDs allows the coating to degrade organic molecules adsorbed on the membrane surface under visible light, and this dynamic self-cleaning surface can become a promising material for biomedical applications.
[0180] 4.1 Material preparation
[0181] 4.1.1. Preparation of CQDs Highly Conductive Carbon Materials
[0182] The CQDs coating material was synthesized by an environmentally friendly, simple and efficient hydrothermal method. First, a mixture of equal proportions of glucose, deionized water and PEG was stirred continuously for 30 minutes at room temperature, where PEG was used as a structural directing agent. The mixed solution was then transferred to a hydrothermal reactor on a polytetrafluoroethylene substrate and reacted at 180°C for 20 hours. Finally, deionized and anhydrous ethanol were used for centrifugal washing three times in sequence, and then placed in a 60°C forced air drying oven to dry overnight to obtain carboxyl-rich CQDs powder.
[0183] 4.1.2 Antifouling coating construction
[0184] The antifouling properties of the nanocomposites were characterized by incubating the SPEC electrodes coated with 5 mg / mL nanocomposites in PBS buffer, cTnI (from Shanghai Medix Biochemica), bovine serum albumin (BSA), myoglobin (Mb), C-reactive protein (CRP), creatine kinase (CK-MB), and patient serum (from Shanghai Chest Hospital) for 60 min, washing with PBS for 5 min, and incubating in a buffer containing 1 M KCl and 5 mM [Fe(CN)6]3- / 4- Cyclic voltammetry was performed in PBS at a scan rate of 100 mV s-1. To characterize the reversibility of the system, bare SPEC electrodes, electrodes covered with noble metal-loaded composite nanomaterials, and electrodes with functionalized nanocomposites were tested.
[0185] 4.1.3 Electrical performance screening
[0186] In order to more precisely and comprehensively evaluate the anti-fouling performance of the sensor, a method for calculating the peak current loss efficiency was introduced. Two η values were proposed in this method, among which η1 = [I0(PBS)-I(X-PBS)] / I0(PBS)*100%; it represents the current density loss caused by the anti-fouling carbon material after coating compared with before coating. η1 intuitively shows the current loss caused by the carbon material itself to the immunosensor. This loss may be due to the electrode passivation caused by the mismatch of electrical properties or poor conductivity, which makes the electron transition require higher energy; η2 = [I(X-PBS)-I(X-Mb)] / I(X-PBS)*100%, which represents the current density loss caused by pollutants in the immunosensor simulated clinical environment after coating with the anti-fouling coating. η2 can clearly describe the self-cleaning ability of the immunosensor for complex proteins under the support of the anti-fouling coating.
[0187] Based on this, four conductive carbon materials with self-cleaning function were first selected, and the SPEC / p-COF / PtAg NWs immunosensor was used as the sensing platform. They were coated on the surface of the electrode material by titration, and incubated in a 37℃ biological drying oven, followed by DPV electrical testing. The test results are as follows Fig.30 As shown in (ad), CQDs exhibited minimal current loss at both η1 and η2. Obviously, CQDs with self-cleaning function caused minimal current density loss to the sensor and exhibited optimal anti-fouling ability.
[0188] Then, the peak current of the immunosensor incubated with the self-cleaning coating was measured in a complex medium environment, in which four common clinical markers, Mb, CRP, CK-MB and BSA, were selected as the polluted environment, and the immunosensor without antifouling material coating was used as the control group. Fig.31 As shown in (a), in the case of uncoated CQDs, the current density directly shows a sharp drop of up to 30%, which is likely to cause false positives in healthy patients, such as Fig.31 As shown in (bd), under the action of CQDs, the immunosensor showed a current density loss of less than 7.6% even in a variety of complex media environments, once again confirming that CQDs are a good choice as an anti-fouling coating.
[0189] Results and discussion
[0190] 4.2.1 CQDs@PDA-real serum and interference test
[0191] In order to explore the clinical applicability and self-cleaning benefits of the constructed antifouling coating, actual measurements were performed on real serum samples, which came from the Department of Critical Care Medicine, Shanghai Chest Hospital. In order to minimize the impact of experimental variables on the measurement results, we used PBS buffer to dilute the single sample to different degrees (1X-100X), thereby obtaining serum samples with a gradient effect, such as Fig.32 As shown in (a), the electrode plays a significant role in identifying the immune markers in the serum, and the peak current shows a significant gradient change. It is worth noting that, unlike the direct measurement of purified cTnI, the addition of serum directly leads to partial current loss. This may be due to the increase in contaminating proteins in the complex serum environment, which leads to electrode polarization. However, compared with the immunosensor without incubation of CQDs@PDA coating, this current loss is negligible. Fig.32 (b) shows the error current values under different serum concentrations. Through linear fitting, it is found that the linear detection range of the sensor is 5.fg / mL-1μg / mL, the fitting equation is I=-78.4lgCcTnI+2.35, R2 is 0.99 (N=8), and the detection limit (LOD) is 0.06ng / mL (S / N=3). It can be seen that the presence of the antifouling coating greatly improves the sensitivity of the sensor, and its linear detection range is further reduced to the fg level, which meets the critical value definition for cTnI detection in clinical diagnosis. The construction of this coating makes early monitoring of myocardial infarction possible and further improves the clinical applicability of the immunosensor.
[0192] Subsequently, to verify the universality of the immunosensor incubated with the coating, e.g. Fig.33 As shown in (a), microRNA-133a was measured for the above-mentioned diluted patient serum. After incubation with different concentrations of patient serum, the immunosensor also showed differences in peak current response. As the serum concentration decreased, the current density decreased successively. Similar to cTnI, microRNA and the probe complementarily bound to produce immune complexes, resulting in a blocking effect, which hindered the electron transfer process. Fig.33(b) shows the linear relationship of peak current and error bar analysis after multi-electrode gradient measurement. The results show that there is a linear correlation in the concentration range of 5fM-1μM, R2 is 0.99 (N=8), the linear equation is I=-42.2lgCmicroRNA-133a+1.17, and the LOD is as low as 0.052fM (S / N=3). It also meets the critical value of clinical detection, proving that the immunosensor can be used for rapid diagnosis and early monitoring of clinical assistance, and has a certain universality. It is worth noting that compared with the electrode without incubation coating material, the linear detection range of the sensor is widened, and its detection limit is further reduced while ensuring sensitivity. Even in the presence of serum contaminants, the electrode's ability to discriminate the immune complex formed by complementary base pairs is not attenuated, and the current density loss is weak, which makes up for the performance loss caused by the complex environment of serum, which makes it possible to achieve multi-channel detection.
[0193] The SPEC / p-COF / PtAg NWs immunosensor before and after CQDs@PDA antifouling coating was subjected to continuous DPV testing within 10 days to observe its long-term self-cleaning ability. The test conditions were room temperature, air, and an environment with simulated clinical pollutants, such as Fig.34 As shown in (a), it can be seen that after CQDs@PDA coating, the peak current decreased by about 8μA. This may be due to the presence of PDA causing partial electrode polarization. As the number of pollution days increased, the immunosensor without anti-fouling coating showed obvious current loss, with η as high as 15.4%, which is very likely to cause false positive cases. The electrode coated with anti-fouling coating only showed a current density loss of η=0.9% after the 10th day, which is negligible compared to the high current density of the sensor itself, fully demonstrating the anti-fouling ability of the coating.
[0194] The sera of 21 patients obtained from Shanghai Chest Hospital were diluted ten-fold and then subjected to electrochemical testing, including sera from 7 patients with myocardial infarction, 7 patients with sepsis, and 7 healthy controls. The test results are as follows: Fig.34As shown in (bd), for the working electrode with cTnI antibody fixed, all 7 patients in the control group were successfully detected, and no false positive cases appeared in the 7 healthy controls; for the working electrode with microRNA-133a probe fixed, all 7 patients and 7 healthy controls were effectively detected; in addition, for the working electrode with CRP antibody fixed, 6 of the 7 patient controls were successfully detected, and all 7 healthy controls were detected. The above serum test results show that the electrochemical immunosensor platform developed based on the p-COF / PtAg NWs composite material coated with CQDs@PDA antifouling coating can realize the parallel joint detection of multiple exosome markers from myocardial infarction, and can effectively distinguish patients from healthy controls, which is expected to be used for early non-invasive screening and health warning of myocardial infarction patients.
[0195] Although the above description is centered on the embodiment, it is only an example and does not limit the present invention. It is clear to those skilled in the art that various modifications and applications not illustrated above can be made within the scope of the essential characteristics of the present embodiment. For example, each component specifically shown in the embodiment can be implemented after being modified. Moreover, various differences related to such modifications and applications should be interpreted as being included in the scope of the present invention as defined in the attached claims.
Claims
1. Application of substrate material / PtAg nanocomposite material in constructing electrochemical immunosensor, characterized by: The base material is selected from MXene or p-COF.
2. The use according to claim 1, characterized in that: The electrochemical immunosensor identifies / detects / sensits myocardial infarction markers and / or sepsis markers.
3. The use according to claim 1, characterized in that: The electrochemical immunosensor detects miRNAs and / or cTnI.
4. The use according to claim 1, characterized in that: The electrochemical immunosensor detects serum samples.
5. A substrate material / PtAg nanocomposite material for constructing an electrochemical immunosensor, characterized in that: The substrate material / PtAg nanocomposite material is MXene / PtAg NPs, or MXene / PtAg NWs, or p-COF / PtAg NPs, or p-COF / PtAg NWs; Wherein, the MXene / PtAg NPs is a composite material of MXene and PtAg NPs with an accordion structure; The MXene / PtAg NWs is a composite material of MXene and PtAg NWs with an accordion structure; The p-COF / PtAg NPs is a composite material of p-COF and PtAg NPs; The p-COF / PtAg NWs is a composite material of p-COF and PtAg NWs.
6. The substrate material / PtAg nanocomposite material according to claim 6, characterized in that: The MXene is obtained by etching MAX-Ti3AlC2 using LiF and hydrochloric acid solution as etching solutions.
7. The substrate material / PtAg nanocomposite material according to claim 5, characterized in that: The preparation method of the MXene / PtAg NPs is as follows: dissolving MXene NSs and CTAB in deionized water and performing ultrasonic treatment until they are completely dissolved; dissolving H2PtCl6 and AgNO3 solutions in the mixed solution; stirring the mixture at a temperature of 90-100° C. for 10-60 minutes; Subsequently, AA was quickly injected; the mixture was kept at 90-100°C and stirred for 90-120 min; finally, MXene / PtAg NPs were obtained after centrifugation, washing, and drying; The preparation method of the MXene / PtAg NWs is as follows: dissolving MXene NSs in an EG solution of H2PtCl6 and AgNO3; adding a mixed solution of EG and DMF, and magnetically stirring until the mixed solution turns light yellow; Then, KOH was dissolved in the above mixture, and magnetic stirring was performed until KOH was completely dissolved to form a black-green uniform solution; thereafter, the mixed solution was reacted in an autoclave at a temperature of 150-190°C for 2-6 hours; finally, MXene / PtAg NWs were obtained after centrifugation, washing, and drying; The preparation method of the p-COF / PtAg NPs is as follows: dissolving p-COF and CTAB in deionized water and performing ultrasonic treatment until they are completely dissolved; dissolving H2PtCl6 and AgNO3 solutions in the mixed solution; stirring the mixture at a temperature of 90-100° C. for 10-60 minutes; Subsequently, AA was quickly injected; the mixture was kept at 90-100°C and stirred for 90-120 min; finally, p-COF / PtAg NPs were obtained after centrifugation, washing, and drying; The p-COF / PtAg NWs were prepared by dissolving p-COF in an EG solution of H2PtCl6 and AgNO3; adding a mixed solution of EG and DMF, and stirring the mixture by magnetic stirring until the mixed solution turned light yellow; Subsequently, KOH was dissolved in the above mixture and magnetically stirred until KOH was completely dissolved to form a black-green uniform solution; thereafter, the mixed solution was reacted in an autoclave at a temperature of 150-190° C. for 2-6 hours; finally, p-COF / PtAg NWs were obtained after centrifugation, washing, and drying.
8. The substrate material / PtAg nanocomposite material according to claim 5, characterized in that: The method for constructing the electrochemical immunosensor is as follows: EDC and NHS are added to the prepared cardiac troponin antibody Ab solution, and the solution is placed on a shaker for 10-20 minutes to activate the antibody surface carboxyl groups; The activated Ab solution was added to the surface of the SPEC / substrate material / PtAg nanocomposite electrode, and the reaction was incubated at 37°C for 60-100 minutes. After the reaction, PBS was used to wash the electrode, and BSA was added to the surface of the electrode and incubated for 30-60 minutes to block the surface active sites. Finally, PBS was used to wash away the unbound BSA to obtain a SPEC / substrate material / PtAg nanocomposite / Ab / BSA electrode.
9. The substrate material / PtAg nanocomposite material according to claim 5, characterized in that: When the electrochemical immunosensor is used to detect microRNA-133a, the incubation method of the electrode is as follows: the substrate material / PtAg nanocomposite solution is titrated on the working electrode, and after drying using a constant temperature heating stage, a customized anti-microRNA-133a DNA sequence probe is attached to the surface of the SPEC working electrode deposited with the substrate material / PtAg nanocomposite, and the probe is customized with C6-SH at the "5'-" end and methylene blue at the "3'-" end.
10. The substrate material / PtAg nanocomposite material according to any one of claims 1 to 11, characterized in that: The base material / PtAg nanocomposite material is coated with a CQDs anti-fouling coating.